Innate Immune Recognition: An Issue More Complex Than Expected - Klara Kubelkova; Ales Macela (Frontiers in Cellular and Infection Microbiology, 2019)
Primary interaction of an intracellular bacterium with its host cell is initiated by activation of multiple signaling pathways in response to bacterium recognition itself or as cellular responses to stress induced by the bacterium. The leading molecules in these processes are cell surface membrane receptors as well as cytosolic pattern recognition receptors recognizing pathogen-associated molecular patterns or damage-associated molecular patterns induced by the invading bacterium. In this review, we demonstrate possible sequences of events leading to recognition of Francisella tularensis, present findings on known mechanisms for manipulating cell responses to protect Francisella from being killed, and discuss newly published data from the perspective of early stages of host–pathogen interaction.